African Medicines Agency: How it will change the landscape of medicines in Africa - Molly Unoh Ogbodum; Deborah Oluwaseun Shomuyiwa; Don Eliseo Lucero‐Prisno III; Comfort Tanaka Gutu; Hajar Bouali; Buya Nabie Bangura; Moussa Fofana; Mohamed Babiker Musa; Hassan Ali Daoud; Priscilla Owusu‐Mensah; David Do Céu Fiagan; Cynthia Amaning Danquah; et al. (Wiley, 2023)
Abstract The African continent, with a population of about 1.2 billion, faces limited access to safe, high‐quality and effective medicine, resulting in a disproportionate disease burden. However, the scarcity of pharmaceuticals has been a significant problem for decades. The need to scale up local production of medicines in Africa is apparent, as over 70% of drugs available in the continent are imported. Africa's pharmaceutical manufacturing industry capacity is subpar due to inadequate production equipment and substandard operations. Inadequate pharmaceutical supplies encouraged the circulation of fake drugs, and the COVID‐19 pandemic highlighted the dangers of the continent's reliance on foreign supplies. Africa's porous borders create ease for drug counterfeiting, with little likelihood of detection once in the supply chain. The African Medicines Agency (AMA) was founded to model the European Medicines Agency to enhance regional drug production, regulation and patient access. The African Union's AMA is a specialized health organization tasked with enhancing regulatory harmonization of medicines, particularly in pharmaceutical production, to increase access to high‐quality medications across the continent. Africa's healthcare industry, particularly domestic pharmaceutical manufacturing, will be a significant economic engine for the continent over the next 5 years. The establishment of AMA is a call to action for governments and regulators to enable Africa to manufacture 60% of the vaccines needed on the continent by 2040.